Stealing Secrets, Telling Lies : How Spies and Codebreakers Helped Shape the Twentieth Century - Gannon, James (Book collections on Project MUSE., 2001)
The interception of the Zimmerman Telegram, the deciphering of the German Enigma machine, the Soviet's damaging penetration of the British Foreign Service through the "Cambridge Five" spy ring, and the U.S. counterintelligence coup known as Operation Venona (which remained classified until 1995) are just some of the dramatic episodes detailed here."--Jacket